Environmental Challenges to South Asian Countries - Awan, Abdul Ghafoor (Asian Accounting and Auditing Advancement, 2015)
Introduction: Growing environmental pollution and its impact on human beings and other living organisms are the major issue confronting the world economy. There is worldwide movement to control expanding pollution and lessening its negative effects. The economists have made extensive studies to measure the impact of environmental pollution on economic development. Objective: The objective of this study to investigate into the causes of environmental pollution and its impact on economic development in South Asia and policy initiatives taken by different stakeholders to reduce its negative effects. Research Problem: The research problem of this study is to investigate “Environmental Challenges to South Asian Countries and their impact on their economies and societies”. The author has analyzed socio-economic impact of environmental degradation in South Asian countries. Methodology: The methodology of the study is descriptive in nature because it mostly involves the description of environmental issues and suggesting the ways how they can be solved? However, different statistical techniques such as time series and panel data analysis have been used to measure socio-economic impact of environmental degradation. Data and Source: The author has used secondary data in this study because it was not possible to collect primary data due to geographical constraints. Most of the data was taken from World Bank, IMF,Asian Development Bank, Indian Ministry of Environment and Forests, United Nations Environment Program, Economic Survey of Pakistan, relevant research journals and books. Findings: The findings of the study are robust because the author has found that both developed and developing countries are responsible for environmental degradation. The advanced countries are using excessive recourses to produce surplus goods while the developing countries are exploiting their natural resources under compulsion to feed their growing population. Policy failure has been noted at both ends due to their divergent economic interests. The author suggest that its viable solution is to give market price to environmental resources and impose tax on the industries responsible for producing pollution in order to discourage them to produce environmental hazards and force them to opt environmental clean technologies, besides creating general awareness in the masses.